Pembinaan dan Simulasi Prospek Budidaya Maggot BSF dengan Sistem Dinamik di Kecamatan Cimenyan Bandung - Vita Sarasi; Iman Chaerudin; Joval Ifghaniyafi Farras (Warta LPM, 2022)
Cimenyan District has a problem in the form of accumulation of waste which pollutes the environment and endangers health. Another problem is the very high price of animal feed because it has to be imported from abroad. An alternative solution to these two problems is to use the Maggot Black Soldier Fly (BSF). BSF maggot is proven to be able to decompose organic waste, it is also animal feed that has high nutrition. Research objectives: (1) to describe the implementation of community development activities regarding how to cultivate BSF maggot in Cimenyan District, (2) to analyze the results of a simulation on the future prospects for BSF maggot cultivation to motivate training participants and readers regarding its potential. This coaching involved 17 participants which was carried out online and offline. Participants were given modules and then guided to carry out cultivation practices. The author also simulated the prospects for BSF maggot cultivation using the dynamic system method. The output of this research is how to cultivate BSF maggot and simulation results using a dynamic system which shows the potential for very good BSF maggot cultivation in the next ten years that the government needs to consider both in reducing organic waste, as a substitute for animal feed, and as a business product to create a circular economy and also support the Sustainable Development Goals (SDGs) targetsCimenyan District has a problem in the form of accumulation of waste which pollutes the environment and endangers health. Another problem is the very high price of animal feed because it has to be imported from abroad. An alternative solution to these two problems is to use the Maggot Black Soldier Fly (BSF). BSF maggot is proven to be able to decompose organic waste, it is also animal feed that has high nutrition. Research objectives: (1) to describe the implementation of community development activities regarding how to cultivate BSF maggot in Cimenyan District, (2) to analyze the results of a simulation on the future prospects for BSF maggot cultivation to motivate training participants and readers regarding its potential. This coaching involved 17 participants which was carried out online and offline. Participants were given modules and then guided to carry out cultivation practices. The author also simulated the prospects for BSF maggot cultivation using the dynamic system method. The output of this research is how to cultivate BSF maggot and simulation results using a dynamic system which shows the potential for very good BSF maggot cultivation in the next ten years that the government needs to consider both in reducing organic waste, as a substitute for animal feed, and as a business product to create a circular economy and also support the Sustainable Development Goals (SDGs) targets.